2012
DOI: 10.1002/14651858.cd007101.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation for paroxysmal and persistent atrial fibrillation

Abstract: There is limited evidence to suggest that CA may be a better treatment option compared to medical therapies in the management of persistent AF. This review was also unable to recommend the best CA method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 83 publications
1
20
0
Order By: Relevance
“…1,2 With this has come the requirement to simplify and shorten the procedure to meet the exponential increase in patient demand as demographic trends predict an epidemic of this condition. The advent of fluoroscopically guided ‘one-shot’ ablation technologies, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 With this has come the requirement to simplify and shorten the procedure to meet the exponential increase in patient demand as demographic trends predict an epidemic of this condition. The advent of fluoroscopically guided ‘one-shot’ ablation technologies, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…When catheter ablation is used in combination with antiarrhythmic drug therapy, the success rate of achieving normal sinus rhythm was 71% [95% confidence interval (CI), 65-77%], which is superior to antiarrhythmic drug therapy alone at 57% (95% CI, 50-64%) (88). Catheter ablation also produces an AF recurrence rate of 20%, which is superior to the 75% found in those taking antiarrhythmic drug therapy alone (89). A recent systematic review comparing catheter vs. surgical ablation for AF demonstrates higher freedom from AF with surgical ablation (90) though complications, including tamponade and pacemaker implantation rates were higher in those that underwent surgical ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also shown that the success rate is much higher when catheter ablation is used in combination with antiarrhythmic drug therapy, as compared to using antiarrhythmic drug therapy alone [50]. Furthermore, the recurrence rate with catheter ablation was far lower as compared to antiarrhythmic drug therapy alone [51,52]. Overall, radiofrequency catheter ablation is a treatment method that has been shown to enhance the patient’s quality of life and also improves ventricle function in a large portion of patients [53,54].…”
Section: Management and Treatmentmentioning
confidence: 99%